Pengaruh Kualitas Produk, Ketersediaan Produk dan Saluran Distribusi Terhadap Keputusan Pembelian Telur - Aditya Bayu; Budi Santoso; Pawestri Winahyu (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research aims to analyze the influence of product quality, product availability and distribution channels on egg purchasing decisions at UD Edy Horn. The research uses a quantitative approach by collecting data through questionnaires distributed to UD Edy Horn consumers as respondents. The collected data was analyzed using multiple linear regression to test the relationship between product quality variables, product availability, distribution channels and purchasing decisions. The research results show that these three variables have a significant influence on egg purchasing decisions. Product quality which includes freshness, reliability, durability and product consistency makes a positive contribution to consumers' purchasing decisions. Product availability which includes stable supplies, easy access to purchases, product completeness, and equitable distribution are also important factors in driving purchasing decisions. Apart from that, distribution channels that are fast, efficient, reliable and easily accessible to consumers also strengthen the decision to purchase eggs at UD Edy Horn. These findings confirm that optimal management of product quality, product availability and distribution channels can increase customer satisfaction and loyalty while strengthening the company's competitive position in the market. This research provides recommendations for UD Edy Horn management to continue to optimize these three aspects to support sustainable business growth.